The art of the steal [videorecording (DVD)] - Sobol, Jonathan; Russell, Kurt; Baruchel, Jay, 1982-; Winnick, Katheryn; Diamantopoulos, Chris; Stamp, Terence; Dillon, Matt (Anchor Bay Entertainment, 2014)
A third-rate motorcycle daredevil and part-time art thief teams up with his sneaky brother to steal one of the most valuable books in the world.